The relationship of director's remuneration and external audit fees between bankruptcy for manufacturing companies listed under PN17 Bursa Malaysia / Nur Ashikin Awang Amin - Awang Amin, Nur Ashikin (2019)
Bankruptcy become an issue among the researcher. This study aim to determine the Relationship of Director’s Remuneration and External Audit Fees Between Bankruptcy For Manufacturing Companies listed under PN17 Bursa Malaysia. The data used in this research is secondary data which are Annual report from 2010-2019. The sample of companies used is 10 of manufacturing companies listed under PN17 in Bursa Malaysia. Panel regression analysis method is used for data analysis. The results of this study indicate that value of adjusted R-square of 0.0017 indicates that bankruptcy can be explained by director’s remuneration and external audit fees. Simultaneously, director’s remuneration and external audit fees shows a positive significant relationship towards the bankruptcy.